Enhancing Social-Emotional Development in Kindergarten: A Study on the Impact of Group A Project Methods - Khoiriyati, Salis; Hoiriah, Hoiri (Interdisciplinary Journal of Social Sciences, 2024)
Children's social-emotional development is a process through which they learn to adapt and understand situations and emotions in their interactions with others, by listening, observing, and imitating what they see. Early childhood social-emotional skills contribute to positive social development, fostering empathy, sympathy, and a mutual need for one another. This study aims to investigate: 1) an overview of the social-emotional abilities of children in Group A at Dharma Wanita Kembangbelor Kindergarten, and 2) the effect of the project method on children in Group A at Dharma Wanita Kindergarten. The study examines the influence of social-emotional abilities among Group A early childhood students at Kindergarten Dharma Wanita Kembangbelor, located in Pacet District, Mojokerto Regency. This research adopts a pre-experimental design, utilizing a one-group pretest-posttest approach with nonprobability sampling conducted through purposive sampling. Data collection techniques include observation, administration of pretest-posttest items, and documentation. Data analysis employs paired sample t-tests with the assistance of SPSS application version 26 for Windows. The results reveal a significant influence of the project method on social-emotional abilities at Kindergarten Dharma Wanita Kembangbelor Pacet. This is evidenced by the increase in the average social-emotional abilities of children from 30.16 to 46.92 following the treatment. Hypothesis testing further confirms this influence, with a sig. value <0.05.